ANALISIS KEPUASAN KONSUMEN PADA PEMBELIAN PRODUK DI ADITI COFFEE HOUSE AND SPACE - Rizki Darmawan Karmana; Dini Rochdiani (Universitas Galuh Ciamis, 2020)
ABSTRACTIndonesia coffee production in 2017 reached 668,88 thousand tons. The level of coffee demand in Indonesia has continued to increase in the last five years. This means that the level of coffee consumption in Indonesia continues to increase. The increasing consumption of coffee in Indonesia is used by businesses to open coffee shops. Coffee shops have become a trend or lifestyle, especially in the city of Bandung. In 2017-2019, there were 85 coffee shops scattered in every corner of the city of Bandung. The rise of the presence of coffee shops make consumers have a choice or option which coffee shop to visit. Consumer satisfaction is one important factor to lure consumers to always be the first choice. Consumer satisfaction is an expression of customer feelings that arise from the results of an evaluation after comparing what is obtained with what is expected. Aditi Coffee House and Space is one of the coffee shops that has problems in identifying the characteristics and ratings of consumers as an evaluation material in order to continue to compete amid the growing presence of coffee shops in the city of Bandung. The design in this study used a qualitative design with descriptive analysis assisted with customer satisfaction analysis tools using the Customer Satisfaction Index (CSI) method. Consumer satisfaction index figures show lift 93.25% which means very satisfied.